Use of the PCR in a Combined Methodological Approach for the Study of Human Fascioliasis in an Endemic Area - Carnevale, Silvana (2020)
Fil: Carnevale, Silvana. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.